A revision of the Lutrochidae (Coleoptera) of Venezuela, with description of six new species - Maier, Crystal A.; Short, Andrew E.z. (Zootaxa, 2013)
The species of Lutrochidae occurring in Venezuela are revised. The only previously recorded species, Lutrochus acumi-natus Grouvelle, is redescribed and a lectotype is designated. Lutrochus vestitus Sharp, is recorded from Venezuela and French Guiana for the first time. Six new species Lutrochus gustafsoni n. sp., L. cauraensis n. sp., L. maldonadoi n. sp., L. meridaensis n. sp., L. minutus n. sp., and L. violaceus n. sp. are described. Notes on habitat and habits for most species are provided, as well as a key to the eight species of Lutrochidae occurring in Venezuela. The family is reported from hy-gropetric habitats for the first time.